G169(P) Exploring ethnic variation in infants with congenital heart defects undergoing paediatric cardiac surgery. (27th April 2015) - Knowles, RL; Ridout, D; Crowe, S; Tregay, J; Wray, J; Barron, D; Cunningham, D; Parslow, R; Franklin, R; Bull, C; Brown, K
Abstract : Introduction: North American researchers have reported ethnic differences in the prevalence and short-term outcomes of congenital heart defects (CHDs), which may reflect genetic variation, environmental exposures or healthcare access. It is unclear whether ethnic differences in CHD frequency and outcomes also exist in the UK population and healthcare system. Aim: To examine national paediatric cardiac surgical audit data for ethnic differences in the frequency of different CHD subtypes, associated comorbidities and short-term outcomes for infants operated in the first year of life. Methods: Individual records from the national congenital cardiac surgical audit (NICOR) of UK infants aged under 12 months who had a cardiac surgery or intervention between 01/01/2005 and 31/12/2010, were matched with intensive care admission records in the Paediatric Intensive Care Audit Network (PICANET) and linked records were obtained for 8481 (86%) of operated infants. Census-derived categories for ethnic classification were used. Results: Children who were operated within the first year of life for major CHD represented 2.2 (95% Confidence Intervals [CI] 2.2, 2.3) per 1000 live births. Compared with children of white ethnicity, children of Asian ethnicity were more likely to have cardiac surgery (2.3 [2.3, 2.4] and 3.2 [3.0, 3.5] per 1000 live births respectively) in the first year of life. CHD subtypes that were significantly over-represented within the Asian ethnic group included single ventricle (SV), transposition of the great arteries, pulmonary atresia, tetralogy of Fallot (TOF) and septal defects; in the Black ethnic group, atrioventricular septal defect and SV were over-represented, while TOF and aortic stenosis were under-represented. Preterm birth occurred in 14% of babies, almost twice the general population rate, and associated non-cardiac anomalies were reported in 21% of affected infants, however no significant ethnic variation was observed. There were 246 deaths during the first year after hospital discharge following surgery but no significant ethnic differences in short-term mortality were identified. Conclusion: The risk of CHD intervention in infants aged under one year varied by ethnic group, and children of Asian ethnicity were at greater risk. No ethnic differences in short-term post-discharge mortality were identified, however longer-term outcomes should be explored.